Enhanced Oxygen Utilization Efficiency With Concomitant Activation of AMPK-TBC1D1 Signaling Nexus in Cyclophilin-D Conditional Knockout Mice - Radhakrishnan, Jeejabai; Baetiong, Alvin; Gazmuri, Raúl J. (Frontiers in Physiology, 2021)
We have previously reported in HEK 293 T cells and in constitutive cyclophilin-D (Cyp-D) knockout (KO) mice that Cyp-D ablation downregulates oxygen consumption (VO2) and triggers an adaptive response that manifest in higher exercise endurance with less VO2. This adaptive response involves a metabolic switch toward preferential utilization of glucose via AMPK-TBC1D1 signaling nexus. We now investigated whether a similar response could be triggered in mice after acute ablation of Cyp-D using tamoxifen-induced ROSA26-Cre-mediated (i.e., conditional KO, CKO) by subjecting them to treadmill exercise involving five running sessions. At their first treadmill running session, CKO mice and controls had comparable VO2 (208.4 ± 17.9 vs. 209.1 ± 16.8 ml/kg min−1), VCO2 (183.6 ± 17.2 vs. 184.8 ± 16.9 ml/kg min−1), and RER (0.88 ± 0.043 vs. 0.88 ± 0.042). With subsequent sessions, CKO mice displayed more prominent reduction in VO2 (genotype & session interaction p = 0.000) with less prominent reduction in VCO2 resulting in significantly increased RER (genotype and session interaction p = 0.013). The increase in RER was consistent with preferential utilization of glucose as respiratory substrate (4.6 ± 0.8 vs. 4.0 ± 0.9 mg/min, p = 0.003). CKO mice also performed a significantly higher treadmill work for given VO2 expressed as a power/VO2 ratio (7.4 ± 0.2 × 10−3 vs. 6.7 ± 0.2 10−3 ratio, p = 0.025). Analysis of CKO skeletal muscle tissue after completion of five treadmill running sessions showed enhanced AMPK activation (0.669 ± 0.06 vs. 0.409 ± 0.11 pAMPK/β-tubulin ratio, p = 0.005) and TBC1D1 inactivation (0.877 ± 0.16 vs. 0.565 ± 0.09 pTBC1D1/β-tubulin ratio, p < 0.05) accompanied by increased glucose transporter-4 levels consistent with activation of the AMPK-TBC1D1 signaling nexus enabling increased glucose utilization. Taken together, our study demonstrates that like constitutive Cyp-D ablation, acute Cyp-D ablation also induces a state of increased O2 utilization efficiency, paving the way for exploring the use of pharmacological approach to elicit the same response, which could be beneficial under O2 limiting conditions.